1997
DOI: 10.3164/jcbn.23.33
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring the Chemopreventive Potential of the Plant Products Neem and Turmeric in 4-Nitroquinoline 1-Oxide-Induced Oral Carcinogenesis.

Abstract: SummaryThe

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
3
8
0
Order By: Relevance
“…Enhanced lipid peroxidation combined with depletion of antioxidants in the liver and circulation of tumor-bearing hamsters observed in the present study is a characteristic finding in malignant transformation [18,27,28]. Administration of neem leaf extract reversed the changes induced by DMBA, thus supporting the hypothesis that plant products are effective chemopreventive agents.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Enhanced lipid peroxidation combined with depletion of antioxidants in the liver and circulation of tumor-bearing hamsters observed in the present study is a characteristic finding in malignant transformation [18,27,28]. Administration of neem leaf extract reversed the changes induced by DMBA, thus supporting the hypothesis that plant products are effective chemopreventive agents.…”
Section: Resultssupporting
confidence: 82%
“…Measurement of circulatory markers is non-invasive and reflects the bioavailability of metabolites after sequestration by the tumor cells [17]. Previously, we reported the importance of examining changes in the host liver and circulation in biomonitoring the chemopreventive potential of neem in 4NQ0-induced oral carcinogenesis [18].…”
Section: Discussionmentioning
confidence: 99%
“…Yadav and Rathore [62] observed inhibition of mitotic activity by neem leaf extract. Studies from this laboratory have demonstrated the chemopreventive potential of neem leaf extracts on MNNG-induced forestomach tumours and 4-nitroquinoline 1-oxide induced oral carcinogenesis [63][64][65][66][67][68]. Aqueous as well as alcoholic extracts of neem leaf effectively suppressed DMBA-induced HBP carcinogenesis by modulating the cellular redox status as well as carcinogen-metabolizing enzymes in the target organ, as well as in host liver and blood [61,[69][70][71].…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Circulatory levels of lipid peroxidation and antioxidants are reliable indicators, because they reflect the bioavailability as well as increased utilization to counter lipid peroxidation. 10 This present study aims to evaluate the modifying effects of aqueous extract of T. arjuna bark (TaBet) on circulatory lipid peroxidation, reduced glutathione (GSH), catalase (CAT), superoxide dismutase (SOD) and glutathione peroxidase (GPx) as well as vitamin E and ascorbic acid as biomarkers…”
Section: Terminalia Arjuna (Roxb) Modulates Circulatory Antioxidantsmentioning
confidence: 99%